1992
DOI: 10.1111/j.1432-1033.1992.tb16743.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of N‐acetylglucosamine kinase and N‐acetylmannosamine kinase by 3‐O‐methyl‐N‐acetyl‐D‐glucosamine in vitro

Abstract: During the search for inhibitors of N-acetylneuraminic acid biosynthesis, it was shown that 3-0-methyl-N-acetylglucosamine competitively inhibits the N-acetylglucosamine kinase of rat liver in vitro with a Ki value of 17 pM. N-Acetylmannosamine kinase is inhibited non-competitively with a Ki value of 80 pM. In a human hepatoma cell line (HepG2), 3-O-rnethyl-N-acetyl-~-glucosamine (1 mM) inhibits the incorporation of ''C-N-acetylglucosamine and ''C-N-acetylmannosamine into cellular glycoproteins by 88% and 70%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
(6 reference statements)
1
21
0
1
Order By: Relevance
“…The inhibition was assessed from the reduced activity relative to control without inhibitors. N-propanoylglucosamine and 3-O-Me-GlcNAc were synthesized and characterized as described earlier (24,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition was assessed from the reduced activity relative to control without inhibitors. N-propanoylglucosamine and 3-O-Me-GlcNAc were synthesized and characterized as described earlier (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the geometry of the active center of hMNK, we postulated that modifications at the C6-position of ManNAc could yield potential inhibitors. N-Propanoylglucosamine and 3-O-Me-GlcNAc were described in previous studies to inhibit MNK activity in cell lysates (24,25). The inhibition effect of these substances was tested in this study with purified recombinant hMNK.…”
Section: ␦1mentioning
confidence: 99%
“…After incubation at 25°C for 20 h, 2 l of alkaline phosphatase (1.5 to 7.5 units) in 1.2 mol of glycine-NaOH buffer, pH 10.0, containing 120 nmol of MgCl 2 were added, and the reaction was incubated at 37°C for 30 to 60 min. Three l of each sample were spotted onto plastic-backed cellulose TLC plate (Merck) and developed in 1-propanol, 1 M sodium acetate, pH 5.0, water (7:1:2, v/v/v) for 8 h (43). When the effect of ionic strength was determined, the samples were spotted on Whatman No.…”
Section: Quantitative Assay For Kdn-9-p Synthetase and Neu5ac-9-p Synmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that GlcNAc is linked as a monosaccharide to Ser and Thr residues of nuclear [13] and have led to an accurate assay of glucokinase in the presence of GlcNAc kinase [14]. and cytoplasmic proteins [3].…”
Section: N-acetylglucosamine (Glcnac) Is a Prominent Sugar Inmentioning
confidence: 99%